Hepatoprotective Effects of a Novel Trihoney against Nonalcoholic Fatty Liver Disease: A Comparative Study with Atorvastatin - Hamad Abdulsalam Hamad Alfarisi; Muhammad Bin Ibrahim; Zenab B. Hamad Mohamed; Nuraniza Azahari; Asmah Hanim Bt. Hamdan; Che Anuar Che Mohamad (The Scientific World Journal)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disorder worldwide with no curative therapy. The aim of this study was to investigate the hepatoprotective effects of a novel Trihoney against biochemical and histological manifestations of NAFLD in hypercholesterolemic rabbits. Methodology. Forty-eight male New Zealand white (NZW) rabbits were grouped into normal diet (C), normal diet with 0.6 g/kg/day of Trihoney (C + H), 1% cholesterol diet (HCD), 1% cholesterol diet with 0.3 g/kg/day of Trihoney (HCD + H1), 1% cholesterol diet with 0.6 g/kg/day of Trihoney (HCD + H2), and 1% cholesterol diet with 2 mg/kg/day of atorvastatin (HCD + At.). Animals were sacrificed after 12 weeks of treatment. Serum lipids and liver function test (LFT) were measured prior to and at the endpoint of the experiment for total cholesterol (TC), low-density lipoprotein (LDL-c), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and total bilirubin (T. Bil.). Liver was processed for histopathology study. Liver homogenate was analysed for oxidative stress parameters: superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA). Results. Lipid analysis approved the induction of hypercholesterolemia. A significant elevation (p<0.01) of serum AST and ALT levels showed by the HCD group was compared to C and C + H groups. Trihoney exhibited a significant reduction (p<0.001) of AST and ALT compared to the HCD group. Likewise, AST and ALT reduced significantly in the HCD + At. group (p<0.001). Trihoney supplementation induced significant (p<0.05) enhancement of SOD and GPx activities. Atorvastatin treatment was associated with significant (p<0.05) reduction of SOD and GPx activities in the liver. Trihoney and atorvastatin showed marked (p<0.001) reduction of hepatic lipid peroxidation. Trihoney showed histological protection against progression of NAFLD to nonalcoholic steatohepatitis (NASH). Atorvastatin exhibited no beneficial impact on hepatic architecture. Conclusion. Trihoney was able to maintain normal liver function and showed hepatoprotection against progression of NAFLD to NASH probably through hypocholesterolaemic and antioxidant functions.